1998
DOI: 10.1051/analusis:199826040033
|View full text |Cite
|
Sign up to set email alerts
|

Data treatment in near infrared spectroscopy

Abstract: The near infra red (NIR) takes place between midd l e infrared and visible region of the spectrum. As quartz is tra n s p a rent in near infra red regi o n , t ra n s m i t t a n c e m e a s u rements of liquids can be done using standard s cuvettes and, reflectance measurements of powders can be realised using fiber optics. NIR spectro s c o py is thus a method that re q u i re few or no sample prep a rat i o n . Absorption bands observed in NIR spectra are due to overtones of, mainly, hydrogenic stretching v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
3

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 5 publications
0
32
0
3
Order By: Relevance
“…For parchment, a direct link between lipid content and collagen degradation has, however, still not been demonstrated. absorptions multiple times across the NIR spectrum, it is necessary to extract the useful information using multivariate chemometric data analysis, such as principal component analysis (PCA) [22][23][24][25] or partial least square calibration (PLS) [21,24,25]. The objective of PCA is to reduce the dimensionality (number of variables) of the dataset, but retain most of the original variability in the data.…”
Section: Introductionmentioning
confidence: 99%
“…For parchment, a direct link between lipid content and collagen degradation has, however, still not been demonstrated. absorptions multiple times across the NIR spectrum, it is necessary to extract the useful information using multivariate chemometric data analysis, such as principal component analysis (PCA) [22][23][24][25] or partial least square calibration (PLS) [21,24,25]. The objective of PCA is to reduce the dimensionality (number of variables) of the dataset, but retain most of the original variability in the data.…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded that NIR spectroscopy [4,10,11,[20][21][22][23][24][25][26][27][28][29][30][31][32][62][63][64] has now entered a mature stage of development and is currently the most efficient method of performing both qualitative and quantitative analysis; this method can also be used to characterize the particle characteristics, including the sizes of solid samples. Section II.…”
Section: Discussionmentioning
confidence: 99%
“…As the reflectance of solid samples varies with the concentration, the absorptivity and the scattering coefficient according to the Kubelka Munk theory [22], the NIR spectrum of a solid material depends both on its chemical composition and on its physical properties, such as the particle size and surface characteristics [23][24][25][26].…”
Section: Near-infrared Spectroscopy (Nir)mentioning
confidence: 99%
“…No entanto, as derivadas são também usadas para corrigir deslocamentos de linha base (Chaminade et al, 1998), sendo esta uma das principais causas de sua aplicação, já que ao estar relacionadas à variação da absorbância ao longo do espectro, os espectros que diferem somente no seu nível de linha base apresentarão a mesma derivada. Na figura A.1 ilustra-se um efeito típico da derivação nos espectros NIR.…”
Section: A11 Derivaçãounclassified
“…As diferentes linhas de regressão são interpretadas como produto da dispersão, e os desvios das linhas como a informação química contida nos espectros (Naes e Isaksson, 1994b et al (1985). (Chaminade et al, 1998) (Meglen, 1991). O NIPALS é um algoritmo eficiente para extrair vetores loadings a partir dos espectros na ordem decrescente de suas contribuições à variância nos espectros de calibração (Haaland e Thomas, 1998).…”
Section: A12 Alisamentounclassified